(untitled) (Archives of Pediatrics of Uruguay, 2021)
Introduction: asthma is the most frequent chronic respiratory disease in children. Severe asthma accounts for less than 5% of all pediatric asthma cases, and shows high morbidity rates, healthcare costs, and even mortality. Objectives: to analyze the clinical and functional characteristics, and comorbidities of patients with severe asthma. Material and methods: descriptive, analytical, retrospective, and transversal study on patients with severe asthma, treated at Pereira Rossell Children Hospital Center between 1/1/2019 and 1/1/2020. Inclusion criteria: children and adolescents of between 5 and 15 years of age with a diagnosis of severe and difficult-to-treat asthma. Results: 15 patients included, 9 females, with a mean age of 10.4 years. All patients showed an early onset of symptoms, beginning at preschool age. 8/15 patients’ first-degree relatives had a record of asthma. Tobacco exposure was present in 8/15. Adherence was correct in 6/15. The inhalation technique was adequate in 11/15. Allergic rhinitis was the most frequent comorbidity assessed, present in 12 out of 15 cases, while obesity was present in 3 out of 15 cases. Conclusions: in the period analyzed, severe asthma accounts for 3.8% of all asthma cases. Most were difficult-to-treat asthma cases (11/15) due to underlying modifiable or reversible factors that prevent asthma control.